Evaluation of bad building programme: the case of Johannesburg housing company - Koali, Mots'eoa Evelyn (My University, 2017)
Affordable housing is a major challenge for the low-income households living in the city of Johannesburg. Many jobs are in the city while most of decent and affordable housing is at the city periphery. This creates a disadvantage as low income housing is located far from the area of concentrated commercial and employment opportunities. This group of citizens incur high transport costs to access these opportunities despite being in lower income bracket. Housing for households earning R3 500 per month and below in the inner city of Johannesburg is very limited yet the demand is very high. This forces these households to live in bad buildings as there is limited alternative to formal and decent accommodation available for them. The Bad Buildings Programme (BBP) was one of the interventions that City of Johannesburg (COJ) developed to address bad buildings in the inner city (19992007). BBP aimed to address housing needs for the households earning R3 500 per month and below. The intention was to ensure that bad buildings become viable and productive economic assets. The research aims to determine whether the BBP has met its strategic requirement of providing decent and affordable housing to lowincome households living in the inner city. The data was collected from group of policy makers and officials1 who participated in the BBP who worked in BBP through face to face interviews. The findings show that BBP did not alleviate low income housing in the inner city of Johannesburg. This research concludes that BBP did not fulfil its objective of improving the quality of life of low income inner city residents.
A research report submitted to the Faculty of Engineering and the Built Environment, University of the Witwatersrand, in partial fulfillment of the requirements for the degree of Master of the Built Environment, 2017
Keywords: Urban renewal--South Africa--Johannessburg; Apartment houses, Cooperative--South Africa--Johannesburg; Housing--Finance